2020
DOI: 10.1002/mds.27973
|View full text |Cite
|
Sign up to set email alerts
|

MYORG Mutation Heterozygosity Is Associated With Brain Calcification

Abstract: A BS TRACT: Background: Biallelic mutations in the MYORG gene were first identified as the cause of recessively inherited primary familial brain calcification. Interestingly, some heterozygous carriers also exhibited brain calcifications.Objectives: To further investigate the role of single heterozygous MYORG mutations in the development of brain calcifications. Methods: A nation-wide cohort of Chinese primary familial brain calcification probands was enrolled from March 2016 ---

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The clinical manifestations and neuroimaging features significantly vary among PFBC patients with mutations in different pathogenic genes. In our four patients, the brain CT findings showed widespread and abundant calcifications, which is consistent with the neuroimaging features in PFBC patients with MYORG mutations as reported by Chen et al (Chen et al, 2019;Chen et al, 2020). Compared with other pathogenic genes, brainstem calcifications affecting the pons and cerebellar atrophy could be the prominent features in MYORG mutation carriers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The clinical manifestations and neuroimaging features significantly vary among PFBC patients with mutations in different pathogenic genes. In our four patients, the brain CT findings showed widespread and abundant calcifications, which is consistent with the neuroimaging features in PFBC patients with MYORG mutations as reported by Chen et al (Chen et al, 2019;Chen et al, 2020). Compared with other pathogenic genes, brainstem calcifications affecting the pons and cerebellar atrophy could be the prominent features in MYORG mutation carriers.…”
Section: Discussionsupporting
confidence: 90%
“…We screened a total of 245 Chinese subjects including 21 subjects from 10 possibly autosomal recessive families and 224 sporadic cases. Eight MYORG variants were identified in six sporadic cases, while four of the eight variants were previously reported (c.103A > G, p.M35V; c.782_783GC > TT, p. R261L; c.1092_1097delCTTCGA, p.365_366delFD; and c.1967T > C, p. I656T) (Supplementary Figures S1A-D) (Yao et al, 2018;Forouhideh et al, 2019;Chelban et al, 2020;Chen et al, 2020). Notably, four novel variants in MYORG were identified: two nonsense variants (c.442C > T, p. Q148*; c.972C > A, p. Y324*) and two missense variants (c.1969G>C, p. G657R; c.2033C > G, p. P678R) (Figures 1A-D).…”
Section: Myorg Variants In the Primary Familial Brain Calcification Cohortmentioning
confidence: 92%
“…Thus, MYORG mutations may exhibit dosage-dependent paraclinical and clinical penetrance, with heterozygous variants, nevertheless, being potentially disease causing. 28 Of further note, we considered every carrier of a nonbenign variant with reported brain calcification and any symptom/sign as clinically affected. However, given that some symptoms (eg, headache and depression) are very prevalent in the general population, and may not be caused by a PFBCgene variant, the penetrance of these variants may actually be lower.…”
Section: Discussionmentioning
confidence: 99%
“…However, about half of the 75 carriers of single heterozygous variants in MYORG , reportedly recessive disease gene, that we excluded from analysis (Supplementary Table S3) had calcifications of various severity and patterns, and among those, only one‐third displayed clinical symptoms/signs. Thus, MYORG mutations may exhibit dosage‐dependent paraclinical and clinical penetrance, with heterozygous variants, nevertheless, being potentially disease causing 28 . Of further note, we considered every carrier of a nonbenign variant with reported brain calcification and any symptom/sign as clinically affected.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions adjacent to the regulatory element in the SLC20A2 coding region may also cause PFBC (Pasanen et al, 2017;Cassinari et al, 2020). SLC20A2 expression might be related to the severity of brain calcification to some extent, such as the genetic dosage effect observed in patients harboring MYORG mutations (Chen et al, 2019b(Chen et al, , 2020Grangeon et al, 2019). Some studies have also suggested a dominant negative function of SLC20A2 genetic variations (Kimura et al, 2016;Larsen et al, 2017), with bi-allelic pathogenic mutations in SLC20A2, resulting in more severe brain calcification (de Oliveira et al, 2013;Chen et al, 2019a).…”
Section: Slc20a2 and Pdgfb Dosage And Functional Effect In Brain Calcificationmentioning
confidence: 99%